KORELASI BEBAN KERJA PERAWAT PELAKSANA DAN KESELAMATAN PASIEN DI RUMAH SAKIT HUSADA JAKARTA - Prawitasari, Shinta (Jurnal Kesehatan Holistic, 2017)
Nursing services should focus on patient safety in both the order of the hospital, community and home care. The purpose of this study is to describe the relationship of nursing workload and patient safety at Husada Hospital Jakarta. This research is descriptive correlation with retrospective approach, descriptive cross sectional. This study used 93 samples of nursing schedule data and 93 patient documents. The result shows that proportion of high nursing workload was in January 53,7%, May 51,6%, July 39,8%, and March 35,3%.Proportion of adequate nursing workload was in March 64,5%, July 60,2%, May 48,4%, and January 46,2%. The proportion of patient safety was 19,4%. There is a significant association between the workload of nurses with patient safety. The department of nursing should assess the trend of patient acuity for each nursing unit and using the data to calculate of nursing personnel every shift, to allocate nursing personnel, and supervise as schedule. Develop the culture of safety and eliminate punitive culture from her unit, choosing the champion for patient safety and eliminate non nursing tasks.